Forces on the body during elite competitive platform diving - Harrison, S. M.; Cohen, R. C. Z.; Cleary, P. W.; Barris, S.; Rose, G. (Ninth International Conference on CFD in the Minerals and Process Industries CSIRO, Melbourne, Australia 10-12 December 2012, 2012)
Impact with the water during a 10 m platform dive imparts large forces onto the diving athlete. Wrist and back injuries are common and are thought to be related to cumulative damage from many overload events, rather than one acute high loading event. Experimental measures of forces on the body are im practical and instead computational simulation is appropriate to estimate this loading. A coupled Biomechanical -Smoothed Particle Hydrodynamics (BSPH) model is applied to a reverse pike dive performed by an elite athlete. The skin surface is represented by a mesh that deforms in response to measured skeleton kinematics. Calculations of the impact forces and the transmission of torque through the skeleton are made. The sensitivity of the results of the model to water entry angle is explored. The simulation framework presented shows promise as a tool for coaches to evaluate the performance and safety of diving technique.